Ceramides stimulate caspase‐14 expression in human keratinocytes. Issue 2 (31st January 2013) - Jiang, Yan J.; Kim, Peggy; Uchida, Yoshikazu; Elias, Peter M.; Bikle, Daniel D.; Grunfeld, Carl; Feingold, Kenneth R.
Abstract Caspase‐14 is an enzyme that is expressed predominantly in cornifying epithelia and catalyses the degradation of profilaggrin. Additionally, caspase‐14 plays an important role in the terminal differentiation of keratinocytes. However, how caspase‐14 expression is regulated remains largely unknown. Here we demonstrate that ceramides (C2‐Cer and C6‐Cer), but not other sphingolipids (C8‐glucosylceramides, sphinganine, sphingosine‐1‐phosphate or ceramide‐1‐phosphate), increase caspase‐14 expression (mRNA and protein) in cultured human keratinocytes in a dose‐ and time‐dependent manner. Inhibitors of glucosylceramide synthase and ceramidase increase endogenous ceramide levels and also increase caspase‐14 expression, indicating an important regulatory role for ceramides and suggesting that the conversion of ceramides to other metabolites is not required. The increase in caspase‐14 expression induced by ceramides is first seen at 16 h and requires new protein synthesis, suggesting that the ceramide‐induced increase is likely an indirect effect. Furthermore, ceramides increase caspase‐14 gene expression primarily by increasing transcription. Blocking de novo synthesis of ceramides does not affect caspase‐14 expression, suggesting that basal expression is not dependent on ceramide levels. These studies show that ceramides, an important structural lipid, stimulate caspase‐14 expression providing a mechanism for coordinately regulating the formation of lipid lamellar membranes with the formation of corneocytes.